Compliance With the International Public Sector Accounting Standards Relating to Disclosure in Algeria - Mohammed, Reda Bendoukha; Bouflaja, Kaloum (International Journal of Membrane Science and Technology, 2024)
The present study aims at the highlighting of the disclosure standards in the international public sector accounting standards (IPSAS) as well as the implementation extent in the public accounting system in Algeria through the 18/15 organic law relating to the financial laws, in particular. In addition to that is the highlighting of a number of disclosure standards in international accounting, in general. The study adopted a descriptive, analytical approach to the disclosure standards relating to the public sector. The findings indicated that a number of disclosure standards relating to the public sector are implemented at 60%, which is a significant percentage that significantly contributes to the public sector modernization as well as the establishment of an effective, modern accounting system based on and mirrors transparency.